Biopsychosoziales Belastungsscreening für Patient*innen am Nationalen Centrum für Tumorerkrankungen Heidelberg: multiprofessionelles Supportivscreening in der Routine mittels PROM : best practice - Bugaj, Till Johannes; Wiskemann, Joachim; Weininger, Anne; Walther, Jürgen; Rötzer, Ingeborg; Alt-Epping, Bernd; Müller, Anne-Kathrin; Krug, Mirjam; Jäger, Dirk; Müller-Tidow, Carsten; Dugas, Martin; Dittrich, Tobias; et al. (Die Onkologie, 2025)
The advice and care offered by specialized services such as psycho-oncology, social work, exercise therapy and nutritional therapy or palliative medicine are of considerable importance in oncology today. The specialist services at the National Center for Tumor Diseases Heidelberg/Comprehensive Cancer Center (NCT/CCC) have been recording the needs of cancer patients for many years in a structured multidimensional screening and carry out a so-called biopsychosocial tumor board based on the screening results. The development of the screening, from its origins in the psycho-oncological liaison service at the Surgical University Hospital in Heidelberg from 2003 to the present day, the experience gained and an outlook on future lines of development will be shared in this article.
Gesehen am 27.02.2025